Respuesta :
The equation you are solving is -3(-2) / 6
6 / 6
1
1 is your answer in simplest form.
When a = -2 and -3a is divided by 6, the final answer in simplest form is equal to 1.
Given the following data:
- [tex]-3a[/tex]
- a = -2
To find an answer to the given equation, we would substitute the value of "a" and then divide by "6":
Substituting the value of a, we have:
[tex]-3a = -3 \times -2\\\\-3a = 6[/tex]
-3a = 6
Next, we would divide by 6:
[tex]\frac{6}{6} = 1[/tex]
[tex]\frac{-3a}{6} = 1[/tex]
Read more: https://brainly.com/question/6201432